Innovation in an IoT-Based Smart Biogas Reactor Prototype for Converting Household Organic Waste into Alternative Energy - Zulfahmi Noor; Nurmasitya Kemalaintan; Marvel Dwi Gulan Silindang; Anisa Suliyanti (International Journal of Engineering Continuity, 2026)
Biogas is a gas produced by the anaerobic decomposition of organic matter with the aid of microorganisms; it primarily consists of methane (CH₄), which has a high calorific value and holds potential as an alternative energy source. Biogas production is carried out using a biogas reactor as the fermentation medium. The use of household waste as feedstock aims to generate economical and environmentally friendly energy while reducing waste and water pollution caused by leachate. The development of alternative energy is becoming increasingly relevant amid global energy supply instability, including the impact of geopolitical dynamics in the Strait of Hormuz region, which serves as a major global oil distribution route. With technological advancements, innovations in smart biogas reactors based on the Internet of Things (IoT) enable real-time monitoring and control of process parameters to enhance methane gas production efficiency. This study employs an experimental method to evaluate the effectiveness of a biogas reactor design utilizing IoT devices, with a focus on real-time monitoring of temperature, pH, and methane gas concentration parameters. Based on the test results, the methane gas concentration increased from 14.08 ppm on the first day to 16.79 ppm on the ninth day. Fermentation conditions indicated an increase of 19.25%. The developed system design utilizes an ESP32 microcontroller integrated with DHT11, PH-4502C, and MQ-4 sensors, and employs Blynk and ThingSpeak for data visualization. The selection of sensors was based on considerations of suitability for the application’s needs, ease of integration with the microcontroller, market availability, and cost-effectiveness of implementation.   Test results indicate that the reactor design and system can consistently transmit and present data within an optimal communication range, thereby contributing to improved efficiency, explosion safety, gas leak prevention, and control over the fermentation process in the constructed reactor. During testing, the results showed that the detected gas leak level was 0% throughout the entire observation period. Thus, the system demonstrated a 100% success rate in leak prevention. The implementation of this reactor design supports the development of a more modern, effective, and sustainable renewable energy processing system.